Mudanças no ingresso e na formação de estudantes negros e pardos no ensino superior do Estado do Ceará após a implantação da Lei 12.711 de 29/08/2012 e seus possíveis efeitos no mercado de trabalho - Toledo, Geison Gomes (2022)
This study aims to assess the changes in the number of black and brown students at universities in the State of Ceará and their respective course completion, with the implementation of Law 12,711 of 2012. The number of black and brown students attending higher education and graduated will be analyzed before the implementation of the Law, in the period from 2008 to 2012, and after the implementation of the Law, in the periods from 2013 to 2019. It is intended to perform exercises to compare these results with those of students from other ethnicities and different income classes in an attempt to to isolate the exclusive effect of the Law. This work also addresses the effects of these graduates entering the job market and graduate school.